USM VICE-CHANCELLOR WELCOMES NEW STUDENTS, REMINDS THEM OF USM ASPIRATION TO PRODUCE HOLISTIC AND GLOBAL GRADUATES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, September 2015 Universiti Sains Malaysia (USM) aspires to produce undergraduates who are holistic and who observe more global values in the future.